Students', teachers', and parents', perceptions of individualized-personalized instruction at St. Joseph's School at San Jose, Occidental Mindoro - Gabriel, Amelita G. (Animo Repository, 1979)
This study is an assessment of the individualized system of instruction at St. Joseph's School in terms of the program, its implementation, and the results obtained as perceived by the students, teachers, and parents. The descriptive survey method is used in this study. The data are gathered from 121 randomly-picked students of the total population of the third and fourth year classes, 22 teachers of the total population of the faculty, and 121 randomly-picked parents, also of the third and fourth year students. An opinionnaire is the main instrument used in this study. It contained statements describing the program, implementation, and the results of individualized instruction. The respondents evaluated these components by rating each statement according to the degree of their satisfaction or dissatisfaction with the conditions described by these items. Specific questions are raised and three hypotheses are tested through statistical treatment using the Spearman Rank-Order Correlation Coefficient (p) and Kendall's Coefficient of Concordance (W). The findings show that as a whole, the three groups of respondents, the students, the teachers, and the parents are satisfied with the program, implementation and results of individualized instruction at St. Joseph's School.